PENGEMBANGAN MODUL LINGKARAN BERBASIS PENDEKATAN OPEN-ENDED DI KELAS VIII SMPN 1 BASO - Sulaiman, Sulaiman; Trisoni, Ridwal; Maris, Ika Metiza (Jurnal Pembelajaran MIPA, 2014)
The research is proposed to get module based open-ended approach which are valid and practice on the math topic circle in junior high school. The methodology that use in this study is a developmental research. Subject of this research is 26 students of eigth grade at SMP N 1 Baso. The way of collecting data is by the result of validator scores, the practical was described by observation and questionnaire. All data have been collected was analysed by using statistic descriptive. The result of data analysis come to conclusion, that, This research produces module based open-ended approach on the topic of circle for students of VIII grade are valid and practice. The validity was described by the result of validator scores, where the all validators state that the instrument have been valid based on content and construction, score is 76 %. The practical was described by testing the module to a small group where most of the students were able to learn the module given, score is 79,6 student were able to learn by using module based open-ended approach.Key words: Module, open-ended approach, validity dan practicality, circle